2021
DOI: 10.1101/2021.10.26.465926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KIBRA-PKCγ signaling pathway modulates memory performance in mice and humans

Abstract: Human memory is a polygenic cognitive trait that is fundamental to individual competence. Genome-wide association studies (GWAS) have identified KIBRA as a novel gene associated with human memory performance. KIBRA interacts with AMPA receptors (AMPARs) and proteins essential for synaptic plasticity. The deletion of Kibra in mice impairs synaptic plasticity and learning and memory. However, the molecular basis through which KIBRA regulates dynamic AMPAR trafficking underlying synaptic plasticity is still unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…KIBRA-deficient mice have reduced PKMζ protein levels in the hippocampus and impaired plasticity and memory loss (41,69), which is consistent with a key role for KIBRA in PKMζ stabilization and the maintenance of synaptic plasticity. Our results show that tauKQ high mice, which have reduced KIBRA at synapses (9), also had decreased PKMζ levels in the hippocampus associated with impaired LTP and hippocampus-dependent memory.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…KIBRA-deficient mice have reduced PKMζ protein levels in the hippocampus and impaired plasticity and memory loss (41,69), which is consistent with a key role for KIBRA in PKMζ stabilization and the maintenance of synaptic plasticity. Our results show that tauKQ high mice, which have reduced KIBRA at synapses (9), also had decreased PKMζ levels in the hippocampus associated with impaired LTP and hippocampus-dependent memory.…”
Section: Resultssupporting
confidence: 63%
“…Chemical LTP and IHC Chemical LTP experiments were performed at 14-15 days in vitro (DIV) in extracellular solution (ECS) containing (in mM): 125 NaCl, 5 KCl, 25 HEPES, 1 NaH 2 PO 4 , and 11 Glucose, and 2.5 CaCl 2 (all from Sigma-Aldrich); 0.0005 tetrodotoxin (Abcam); 0.1 picrotoxin (Caymen Chemicals); and 0.001 strychnine (Sigma-Aldrich; pH 7.4) warmed to 37°C. Rat hippocampal neurons were washed in ECS then incubated with 300 μM Glycine (Sigma-Aldrich) in ECS for 5 minutes fractions prepared from KIBRA-KO mice (69). While our study highlighted the critical role for KIBRA in modulating synapse repair to recover memory and showed that PKMζ overexpression alone was not sufficient to restore plasticity in neurons with pathogenic tau, a recent study found that the memory impairments caused by oligomeric amyloid β toxicity in rats were alleviated by PKMζ overexpression in the hippocampus (71).…”
Section: Micementioning
confidence: 99%
“…Phosphorylation is a well-established mechanism for regulating AMPAR trafficking and function. 37 , 71 In addition to serving as a signaling scaffold for regulators of endosomal trafficking, KIBRA regulates a number of kinases 50 , 60 , 72 including PKCγ 73 which was recently reported to play an important role in regulating AMPAR phosphorylation and function 73 . Identifying how different KIBRA-regulated signaling mechanisms intersect to regulate AMPARs, synaptic plasticity, and memory, and how such mechanisms change across development and celltype will be an important focus for future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relevance of all WWC family proteins to disordered brain function, KIBRA is the only WWC family member that has been the subject of mechanistic study in the brain. KIBRA functions as an excitatory synapse scaffold, regulating activitydependent trafficking of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs), which mediate the majority of fast excitatory synaptic transmission in the brain [18][19][20][21] . Deletion of KIBRA causes aberrant trafficking and expression of AMPAR subunits GluA1 and GluA2 in the hippocampus and impairs synaptic plasticity and memory 18,19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…KIBRA functions as an excitatory synapse scaffold, regulating activity-dependent trafficking of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs), which mediate the majority of fast excitatory synaptic transmission in the brain 1821 . Deletion of KIBRA causes aberrant trafficking and expression of AMPAR subunits GluA1 and GluA2 in the hippocampus and impairs synaptic plasticity and memory 18,19,21 . Additionally, loss of KIBRA impairs experience-induced changes in hippocampal and cortical circuit dynamics that support memory consolidation 22…”
Section: Introductionmentioning
confidence: 99%